Polishing Papers for Publication: Palimpsests or Procrustean Beds? - McKenny, John (2012)
Portuguese academic discourse of the humanities is notoriously difficult to render into English, given the prevalence of rhetorical and discourse features that are largely alien to English academic style. The aim of this study was to test the hypothesis that some of those features might find their way into the English texts produced by Portuguese scholars through a process of pragmalinguistic and sociopragmatic transfer. If so, this would have important practical and ideological implications, not only for the academics concerned, but also for editors, revisers, teachers of EAP, translators, writers of academic style manuals and all the other gatekeepers of the globalized culture. The study involved a corpus of some 113,000 running words of English academic prose written by established Portuguese academics in the Humanities, which had been presented to a native speaker of English (professional translator and specialist in academic discourse) for revision prior to submission for publication. After correction of superficial grammatical and spelling errors, the texts were made into a corpus, which was tagged for Part of Speech (CLAWS7) and discourse markers (USAS) using WMatrix2 (Rayson 2003). The annotated corpus was then interrogated for the presence of certain discourse features using Wmatrix2 and Wordsmith 5 (Scott 2006), and the findings compared with those of a control corpus, Controlit, of published articles written by L1 academics in the same or comparable journals. The results reveal significant overuse of certain features by Portuguese academics, and a corresponding underuse of others, suggesting marked differences in the value attributed to those features by the two cultures.